Teaching Grammar and the Communicative Method in Salahaldin Secondary Schools - Fahad, Kawakib Ghazi; Salem, Khalid Nayef (Journal of Tikrit University for Humanities, 2023)
This study aims at investigating the difficulties encountered by teachers in teaching grammar while using the communicative method in Saladin secondary schools. It is hypothesized that most of English teachers use the traditional method of teaching and they don’t use communicative method in teaching grammar, and the second hypothesis is that ‘teachers who teach males students encounter more difficulties in teaching grammar than those who teach female students’. The sample of this study is secondary school students and teachers that teach English as a foreign language. A questionnaire is designed to achieve the aims of the study. Data is collected analyzed statistically. Finally , the findings of the study revealed that teachers of English who teach ‘English for Iraq’ series encounter various difficulties in teaching grammar , and English teachers use the traditional way of teaching grammar (the structural method) ,and they don’t know how to teach grammar contextual lying. According to the findings it has been found out that the students has a significant relationship with the teaching method and this will be reflected on the performance of the students of secondary school students.